2021
DOI: 10.1101/2021.12.10.472085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knockout of liver fluke granulin, Ov-grn-1, impedes malignant transformation during chronic infection with Opisthorchis viverrini

Abstract: Infection with the food-borne liver fluke Opisthorchis viverrini is the principal risk factor for cholangiocarcinoma (CCA; bile duct cancer) in the Lower Mekong River Basin countries including Thailand, Lao PDR, Vietnam, Myanmar and Cambodia. Using gene edited liver flukes in a hamster model of CCA involving concurrent infection and administration of sub-carcinogenic levels of nitrosamine, we explored the role of the fluke granulin-like growth factor Ov-GRN-1 in malignancy. We produced programmed gene knockout… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 97 publications
(200 reference statements)
0
2
0
Order By: Relevance
“…The mutation resulted in reduced pathology when gene-edited parasites colonised the biliary tract of hamsters [ 20 ]. In a recent preprint, these same investigators appeared to confirm a role for liver fluke granulin in malignant transformation of the biliary tract [ 100 ]. Following upon the findings with VSVG pseudotyped MLV, VSVG pseudotyped HIV-1 (human immunodeficiency virus 1) lentiviral virions was also reported to facilitate CRISPR-based transfection of schistosomes [ 80 , 89 ] and to deliver proviral transgenes into the chromosomes of S. mansoni [ 101 ].…”
Section: Advanced Techniques: Crispr/cas9mentioning
confidence: 99%
“…The mutation resulted in reduced pathology when gene-edited parasites colonised the biliary tract of hamsters [ 20 ]. In a recent preprint, these same investigators appeared to confirm a role for liver fluke granulin in malignant transformation of the biliary tract [ 100 ]. Following upon the findings with VSVG pseudotyped MLV, VSVG pseudotyped HIV-1 (human immunodeficiency virus 1) lentiviral virions was also reported to facilitate CRISPR-based transfection of schistosomes [ 80 , 89 ] and to deliver proviral transgenes into the chromosomes of S. mansoni [ 101 ].…”
Section: Advanced Techniques: Crispr/cas9mentioning
confidence: 99%
“…For instance, over 300 proteins have been identified in the ES products from O. viverrini (4), one of which is a granulin-like growth factor termed Ov-GRN-1, which drives proliferation of biliary epithelial cells. Ov-GRN-1-induced cell proliferation can be inhibited with antibodies raised to the recombinant protein (12), and moreover, infection of hamsters with Ov-grn-1 knock-out flukes results in reduced biliary fibrosis and cholangiocarcinoma compared to hamsters infected with control flukes (8,13). In addition, we reported that O. viverrini secretes small extracellular vesicles (EVs) of 40-100 nm in size that can be internalized by host cells (3), and that blocking internalization of these EVs using antibodies against a member of the tetraspanin protein family significantly reduced the secretion of pro-inflammatory cytokines including IL-6 (3).…”
Section: Introductionmentioning
confidence: 99%